Controlled generation and use of CO in flow12. Issue 3 (25th February 2016) - Hansen, Steffen V. F.; Wilson, Zoe E.; Ulven, Trond; Ley, Steven V.
Abstract : A tube-in-tube flow reactor allows the generation and immediate use of CO, without the need for CO cylinders. Abstract : A method for the generation and use of carbon monoxide in flow chemistry has been developed. By using a tube-in-tube reactor, oxalyl chloride can be conveniently and safely hydrolyzed using a NaOH solution to generate CO in the outer stream, which then passes through AF-2400 semi-permeable inner tubing to enrich a reaction stream where it is consumed. The tube-in-tube reactor allows the generation of CO under conditions which would otherwise be incompatible with the reaction conditions. In this way carbonylations can be successfully performed in flow without the use of pressurized gas cylinders. Both alkoxy- and aminocarbonylation was carried out in flow, including a 320 minute continuous run, as proof of concept.